A Midgut Duplication Cyst Lined by Respiratory Epithelium. (12th March 2018) - Mahendran, Balaji; Bracey, Tim; Kochupapy, Rajesh T.
Abstract : Duplication cysts are an uncommon finding. Majority of these cases are found in the region of the midgut, and many have been reported in literature. However, there has been only one previous case of a midgut duplication cyst lined by respiratory epithelium. This is a rare pathology, of which very little is known about. The pathophysiology of these cases is also difficult to explain. We aim to present a case of a midgut duplication cyst in a paediatric patient, who had other abnormalities as well. We also aim to offer a hypothesis for this case.